Annotated checklist of the marine ichthyofauna of Mauritania from shallow-water habitats and artisanal fish markets - Alexander Hans Knorrn; Sidi Mohamed M. Moctar; Moritz Sonnewald; Mamadou Dia; Alioune Niang; André Freiwald (Check List)
Due to their location in a strong upwelling area, Mauritanian waters are one of the most nutrient‑rich and productive areas in the eastern Atlantic Ocean. On the Mauritanian coast, a remarkably high biodiversity consisting of tropical, subtropical, and temperate species with overlapping distributions can be found. This study reports 104 fish species from 53 different families from this area. Overall, the findings indicate Mauritanian waters as a coastal area with high biodiversity and occurrences of several critically endangered elasmobranch species such as Sphyrna lewini (Griffith & Smith, 1834) and Glaucostegus cemiculus (Geoffroy Saint-Hilaire, 1817). Moreover, this survey indicated an urgent need for updates concerning the IUCN Red List classification of several Mauritanian species, which serve as an essential income source for artisanal fishermen in Mauritania.